Modulation Of IgE Levels In Lead Exposed Children By Parental Cigarette Smoking, Qualyobia Governate, Egypt - RAGIA M. HEGAZY; RANIAH HAMDY; HALA F. KAMEL (International Journal of Pharma and Bio Sciences, 2011)
Many children possessing blood lead levels (BLL) in excess of centre of disease control and prevention (CDC) guidelines (>10 µg/dL) exist especially in urban areas with a predominance of housing built early to mid-20th century. In addition, many children are exposed in the home to Parental tobacco smoke (PTS). The current study examined the effect of lead-exposure (BLL levels of 1-55 µg/dL) with/without concurrent PTS exposure on immune system function in 318 children aged 6-84 months from some urban areas, Qualyobia Governate, EGYPT. In this population, 62.9% of children came from smoking homes, 36.5% of children possessed BLL levels >10 µg/dL, 51.9% of children were under 2 years of age, and the population was economically homogeneous. Multiple immune function markers including cell counts, and IgE levels were analyzed for correlation with Pb and / or PTS exposure. For children exposed to both Pb and PTS, a marginally significant relationship between IgE and BLL levels was observed (p=0.12). IgE levels increased in children with combined Pb and PTS exposure. For children exposed to Pb without PTS, decreased lymphocyte cell counts, and serum IgE levels, while granulocyte counts (%granulocytes) was increased. A statistically significant correlation between PTS and BLL levels was found.